2013
DOI: 10.1159/000350542
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Aortic Intima-Media Thickening via Perivascular Adipose Tissue Inflammation

Abstract: Background/Aims: Neointimal thickening results from inflammation in association with vascular smooth muscle cell (VSMC) proliferation. We studied the role of perivascular adipose tissue (PVAT) on VSMC proliferation and intima-media thickening (IMT) in a rodent model of chronic inflammation. Methods: The abdominal aorta and surrounding PVAT of tumour necrosis factor (TNF)-α-injected mice were examined 28 days after administration. Plasma and PVAT cytokines were measured with Milliplex™ assays. Inflammatory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Also, transplantation of PVAT derived from transgenic mice overexpressing adipose tissue-specific angiopoietin like 2 (ANGPTL2) accelerated neointimal hyperplasia induced by wire injury of the femoral artery, which was attenuated by transplantation of PVAT from ANGPTL2 −/− mice [ 189 ]. Moreover, inflamed PVAT increases VSMC proliferation in a TGF-β dependent manner, suggesting that TGF-β released from PVAT can potentiate neointima formation [ 190 ]. Furthermore, as reviewed elsewhere [ 136 ], PVAT-derived factors such as leptin, viafastin, TNF-α, IL-6 and IL-8, promote VSMC proliferation and migration.…”
Section: Cellular and Molecular Contact Between Pvat And The Vessel Wmentioning
confidence: 99%
“…Also, transplantation of PVAT derived from transgenic mice overexpressing adipose tissue-specific angiopoietin like 2 (ANGPTL2) accelerated neointimal hyperplasia induced by wire injury of the femoral artery, which was attenuated by transplantation of PVAT from ANGPTL2 −/− mice [ 189 ]. Moreover, inflamed PVAT increases VSMC proliferation in a TGF-β dependent manner, suggesting that TGF-β released from PVAT can potentiate neointima formation [ 190 ]. Furthermore, as reviewed elsewhere [ 136 ], PVAT-derived factors such as leptin, viafastin, TNF-α, IL-6 and IL-8, promote VSMC proliferation and migration.…”
Section: Cellular and Molecular Contact Between Pvat And The Vessel Wmentioning
confidence: 99%
“…Moreover, inflamed PVAT increases VSMC proliferation in a TGF-β dependent manner, suggesting that TGF-β released from PVAT can potentiate neointima formation (Moe et al, 2013 ) The PVAT transplantation approach has also been used to study the effects of PVAT-derived Angptl2 on the progression of neointimal hyperplasia after endovascular injury (Tian et al, 2013 ). Here, PVAT from mice over-expressing Angptl2 accelerate neointima formation, while PVAT from Angptl2 −/− mice attenuated it.…”
Section: Pvat In Obesity-related Vascular Diseasementioning
confidence: 99%
“…34 Consistent with this, a recent study using a murine model of chronic inflammation via TNF-α injection found that PVAT inflammation led to MMP-mediated TGF-β production, resulting in neointima formation. 80 In addition, vascular injury has been reported to upregulate proinflammatory adipokines and downregulate anti-inflammatory adiponectin in PVAT in both mice and rats. 81 Furthermore, a high-fat diet in mice was found to induce a proinflammatory phenotype in the PVAT.…”
Section: Pathologies In Animal Models With Reduced or Absent Pvatmentioning
confidence: 99%